The Bible and Religious Freedom - Ben-Oni Ardelean (Kairos (English Ed.), 2010)
Religious beliefs influence the acts and behaviors of religious people, most of the time overwriting any social or deontological norm. A brief overview into the dogma of diverse religions that refers directly to religious freedom sheds more light on these behaviors that could not be otherwise explained. Looking into Christianity, things should not be different. According to the understanding of most Christian denominations, the Bible is the only norm for Christian living. Thus biblical doctrines should reveal how to act in regard to religious freedom. Although the Bible is not considered a norm by society at large, only by Christians, it could provide moral principles for those professing the Christian faith that are linked with a normative approach to religious freedom in actual modernity. What does the Bible say about religious freedom? Of what relevance is this to non-Christians? Are Christians aware of these prescriptions? These are extremely important questions for a contemporary multi-religious society, in tension with numerous interreligious or religiously originated conflicts. The aim of this article is to find a solid biblical base for an approach to religious freedom in order for Christians to position themselves on this issue.